2014
DOI: 10.1017/dmp.2014.119
|View full text |Cite
|
Sign up to set email alerts
|

Building a National Model of Public Mental Health Preparedness and Community Resilience: Validation of a Dual-Intervention, Systems-Based Approach

Abstract: Given appropriate guidance, LHDs and FBOs can implement an effective and potentially scalable model for promoting disaster mental health preparedness and community resilience, with implications for positive translational impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…Given these results, our study suggests that stress-reduction interventions among hurricane-affected community members may be particularly useful if implemented at venues such as job fairs and forums on post-hurricane construction, in addition to more typical settings for post-disaster interventions such as mobile clinics in the immediate aftermath, as well as community mental health centers, faith-based organizations, and school settings. [40][41][42] The geographic distribution of the participants shown in Table 1 seems to support the fact that the present study covered a wide geographic area of Long Island, Queens, and Staten Island and involved area known to have had a wide variation in exposures to Sandy. The finding regarding younger age being significantly associated with greater perceived stress confirms previous literature suggesting that younger disaster victims suffer greater impairment than do older adults.…”
Section: Discussionsupporting
confidence: 77%
“…Given these results, our study suggests that stress-reduction interventions among hurricane-affected community members may be particularly useful if implemented at venues such as job fairs and forums on post-hurricane construction, in addition to more typical settings for post-disaster interventions such as mobile clinics in the immediate aftermath, as well as community mental health centers, faith-based organizations, and school settings. [40][41][42] The geographic distribution of the participants shown in Table 1 seems to support the fact that the present study covered a wide geographic area of Long Island, Queens, and Staten Island and involved area known to have had a wide variation in exposures to Sandy. The finding regarding younger age being significantly associated with greater perceived stress confirms previous literature suggesting that younger disaster victims suffer greater impairment than do older adults.…”
Section: Discussionsupporting
confidence: 77%
“…About 25% of participants reported that they provided MHFA to a disaster victim at least once in the 12 months following their training. Most participants confirmed that they were more interested in (89.2%) and more motivated to participate in (78.4%) disaster preparedness training 14 …”
Section: Resultsmentioning
confidence: 96%
“…For example, interviews with disaster response personnel, farmers and animal owners in South Australia about community fire preparedness identified three core practical initiatives: workplace catastrophic day leave, financial incentives to individuals to become bushfire‐ready, and changes to farming practices 12 . A US‐based study examined a dual intervention of mental health first aid (MHFA) and guided preparedness planning to enhance disaster mental health preparedness and community resilience in both urban and rural areas 13,14 . About 25% of participants reported that they provided MHFA to a disaster victim at least once in the 12 months following their training.…”
Section: Resultsmentioning
confidence: 99%
“…GPP workshops were effective in guiding .90% of the urban and rural planning teams in the crafting of disaster plans for their communities. 21 Importantly, the success of early versions of GPP was compromised by attendees who did not possess sufficient knowledge of their FBO leadership to be effective planners, and by trainers devoting too much workshop time to lecturing about disaster planning.…”
Section: Question 22: Evaluation Of Effectivenessmentioning
confidence: 99%